THE DEVELOPMENT AND SEQUENTIAL OSSIFICATION IN THE MARINE CATFISH, TACHYSURUS THALASSINUS (RUPPELL) - Menon, N Gopinatha; Bande, V N; Balachandran, K (Indian Journal of Fisheries, 2011)
The development of Tachysurus thalassinus is described based on experimental rearing of embryos, fromearly embryonic stage to complete absorption of yolk sac. The time taken for development from egg tocomplete absorption of yolk is thirty five days. The progressive ossification of embryonic/larval skeletonis studied with the help of alizarin - red 5 stained, embryonic skeleton at various stages of development.The prominent characters of the species are laid down early in the larval stages and maintainedthroughout the life